2006
DOI: 10.4049/jimmunol.176.5.2942
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Tyrosine 320 Impairs Spontaneous Endocytosis and Enhances Release of HLA-B27 Molecules

Abstract: Several lines of evidence suggest that endocytosis of MHC class I molecules requires conserved motifs within the cytoplasmic domain. In this study, we show, in the C58 rat thymoma cell line transfected with HLA-B27 molecules, that replacement of the highly conserved tyrosine (Tyr320) in the cytoplasmic domain of HLA-B27 does not hamper cell surface expression of β2-microglobulin H chain heterodimers or formation of misfolded molecules. However, Tyr320 replacement markedly impairs spontaneous endocytosis of HLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…The endocytosis of MHC class I molecules is dependent on a sequence in the MHC class I molecule cytoplasmic tail (40,41,47). Studies have indicated that MHC class I molecules are recycled to the cell surface after internalization (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The endocytosis of MHC class I molecules is dependent on a sequence in the MHC class I molecule cytoplasmic tail (40,41,47). Studies have indicated that MHC class I molecules are recycled to the cell surface after internalization (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…6), expression of the ARF6-Q67L mutant, which blocks fusion of ARF6-positive endosomes with early endosomes, results in the accumulation of receptors in vacuole-like structures (49). The requirement for tyrosine-dependent endocytosis of Siglec-F has also been demonstrated for MHC-1 (42,63), although the exact role of this sequence in the endocytic mechanism remains to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…The amino acid epitopes recognized by these antibodies (HC-10, LA45, L31, M38 and HCA2) are indicated [7,8,10,12]. Also indicated are the specific amino acid sequences in the cytoplasmic tail proposed to regulate MHC-I endocytosis and intracellular trafficking [53,60,62].…”
Section: Mhc-i Molecules -Dynamic Structures With a Tendency To Open Upmentioning
confidence: 99%